Effects of continuous cropping on bacterial community diversity and soil metabolites in soybean roots - An, Liwei; Lu, Xinnan; Zhang, Pengyu; Sun, Jiayao; Cong, Baiming; Sa, Rula; He, Dexin (Frontiers in Microbiology, 2025)
The alternating planting of corn and soybeans is regarded as an effective strategy in addressing the challenges faced in soybean cultivation. However, the precise mechanisms that control the bacterial microbiome in soybean roots in the soil, particularly in continuous cropping and rotational corn–soybean farming rotations, are remain unclear. This study employed both field and pot positioning experiments, using high-throughput and generic metabolomics sequencing techniques to explore the dynamics between soybean plants, root microflora, and soil metabolites, especially in the context of continuous cropping and fluctuating corn–soybean crop rotation. The process that included rotating corn soybeans significantly enhanced their grain yield, dry weight, soil nitrogen concentration, urease activity, as well as the accumulation of nitrogen, phosphorus, and potassium in various plant organs, compared to the traditional practice of continuous soybean cultivation. There is a significant reduction in the transit of bacterial operational taxonomic units (OTUs) from the rhizosphere to the endosphere through rhizoplane. The number of bacterial OTUs that are consumed and enriched on rhizoplane is greater than those that are enriched and absorbed in the endosphere. Continuous cropping practices significantly boost Burkholderiales, whereas chloroplast microorganisms significantly improve crop rotation techniques. Soil environmental factors, such as urease and accessible phosphorus, are crucial in establishing the relative prevalence of Rhodanobacter and other bacterial groups. Soil metabolites, such as benzyl alcohol, show a positive correlation with Cyanobacteria, while acidic compounds, such as D-arabinitol, are positively linked with Burkholderiales. This study indicates that the rotation of corn and soybean crops facilitates the growth of soybeans, increases nutrient accumulation in both plants and soil, enhances the presence of beneficial bacteria, and improves soybean yields.